ANALYSIS OF STRATEGIES FOR IMPROVING PUBLIC SERVICES AT THE BARUGA SUBDISTRICT OFFICE, KENDARI CITY - Auliany Hasan, Reski; Marlina, Siti; Pratama Mandala Putra, Ryan; Agus Mokodompit, Eliyanti (Qawwam : The Leader's Writing, 2025)
Public service is a crucial indicator for assessing local government performance and community satisfaction. This study aims to analyze strategies for improving public services at the Baruga Subdistrict Office, Kendari City, focusing on service quality from the perspective of the community and the influencing factors. This research employs a descriptive qualitative approach, with data collected through observation, semi-structured interviews, and documentation. Informants include the Head of the Subdistrict, service staff, and community service users, selected using purposive sampling until data saturation was reached. Data analysis was conducted using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The results indicate that the quality of public services at the Baruga Subdistrict Office is generally good, particularly in the dimensions of tangibles, reliability, responsiveness, assurance, empathy, competence, credibility, and security. However, several aspects require improvement, including facility comfort, staff proficiency in using supporting tools, and friendliness in service interactions. Recommended strategies for service improvement include employee training, facility enhancement, strengthening standard operating procedures, and fostering empathetic and professional attitudes. These findings emphasize the importance of employee competence, facility quality, and interactions with the community as key factors in enhancing public satisfaction.